Pasilan aluesuunnitelma 2013-2022 - Arponen, Petri; Saukkonen, Tiina; Tuominen, Taina; Rapola, Eeva; Tolvanen, Kati; Helsingin kaupunki. Rakennusvirasto (Helsingin kaupungin rakennusviraston julkaisuja, ISSN 1238-9579, 2012)
Sammandrag.